Density Functional Theory Study on Conformers of Benzoylcholine Chloride - Mustafa Karakaya; Fatih Ucun; Ahmet Tokatlı (Journal of Spectroscopy)
The optimized molecular structures and vibrational frequencies and also gauge including atomic orbital (GIAO) 1H and 13C NMR shift values of benzoylcholine chloride [(2-benzoyloxyethyl) trimethyl ammonium chloride] have been calculated using density functional theory (B3LYP) method with 6-31++G(d) basis set. The comparison of the experimental and calculated infrared (IR), Raman, and nuclear magnetic resonance (NMR) spectra has indicated that the experimental spectra are formed from the superposition of the spectra of two lowest energy conformers of the compound. So, it was concluded that the compound simultaneously exists in two optimized conformers in the ground state. Also the natural bond orbital (NBO) analysis has supported the simultaneous exiting of two conformers in the ground state. The calculated optimized geometric parameters (bond lengths and bond angles) and vibrational frequencies for both the lowest energy conformers were seen to be in a well agreement with the corresponding experimental data.